Art Pedagogy Methods In The Development Of Creativity In Primary School Students - Dauletmuratova, Bayramgul (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article examines art pedagogy methods as an effective tool for developing the creativity of primary school students. The pedagogical potential of artistic and creative activity in the formation of imagination, originality of thinking, and the ability to express oneself in primary school students is substantiated. The main art-pedagogical methods used in the primary school learning process are analyzed, and their developmental possibilities are revealed. The conclusion is made about the expediency of systematically implementing art-pedagogical methods in the educational practice of primary education.